Development of Employability Skills of Hospitality Students through Interactive Multimedia Approaches at Medan Tourism Polytechnics - Femmy Indriany Dalimunthe; Muhammad Halfi Indra Syahputra (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The article aims to analyze how to develop employability skills for Medan tourism polytechnic students through a multimedia system approach at the Medan tourism polytechnic. By interviewing several academics at the Medan Polytechnic tourism Department, we have obtained valuable data, including how academicians prepare students to develop their working skills in the hospitality world with a technological approach. We designed this study qualitatively with semi-structured interviews and reviewed secondary data. We finally got some valuable input. The coordinators and lecturers of the Medan Tourism Polytechnic have developed the abilities of their students who are ready to enter the world of a career in the future. The skills they prepared include, for example, being flexible workers, having industry awareness then, having attention to detail skills, time management, interpersonal skills and communication skills, and so on. Hopefully, these findings will become input for developing help studies and labeling skills for future students. Keywords: Employability Skills, Multimedia Interactive, Multimedia Approaches